Worst case - Patterson, James, 1947- (Grand Central Pub., 2013)
Detective Michael Bennett and FBI Abduction Specialist Emily Parker reluctantly team up to stop a killer targeting not only the children of New York's wealthiest families--but the entire city of New York.